2018
DOI: 10.1002/pen.25015
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of COF‐LZU‐1 into the terpolyimide matrix to obtain COF‐LZU‐1/terpolyimide composites with ultra‐low dielectric constant

Abstract: Polyimides are used in microelectronics as they possess the essential high tensile properties, high thermal stability and low dielectric constant. As the further reduction in their dielectric constant is indispensable for such applications, in this study it was loaded with the porous covalent organic framework (COF‐LZU‐1) to obtain COF‐LZU‐1/terpolyimide composites. The composites can capture much air (κ = 1) in their matrix and bring down the dielectric constant below the virgin polyimides. In the beginning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Similar to the simulated LZU-1, the synthesized LZU-1 had a peak at about 4.7°, which indicated that the material had a certain degree of crystallinity. 46 For the composite material IL- x ( x = 1–3), all diffraction patterns showed the four characteristic peaks of In 2 S 3 , and the characteristic peak of HLZU-1 at about 20° was slightly enhanced. On the one hand, this is because In 2 S 3 has a characteristic peak at 20.3°.…”
Section: Resultsmentioning
confidence: 93%
“…Similar to the simulated LZU-1, the synthesized LZU-1 had a peak at about 4.7°, which indicated that the material had a certain degree of crystallinity. 46 For the composite material IL- x ( x = 1–3), all diffraction patterns showed the four characteristic peaks of In 2 S 3 , and the characteristic peak of HLZU-1 at about 20° was slightly enhanced. On the one hand, this is because In 2 S 3 has a characteristic peak at 20.3°.…”
Section: Resultsmentioning
confidence: 93%
“…The catalysts keep thermally stable below 400 °C and start to sharply decompose at 400 °C. 21,37 The weight loss assigned to pure HPW below 300 °C is due to the removal of physically adsorbed water and crystal water (Figure S1B), and the gradual weight loss from 500 to 900 °C originates from the decomposition of the Keggin anion. 38 Based on the TGA curves of the catalysts, the HPW/LZU1 mass ratio values were calculated for cross checking (Table 1), and they were found to be very close to the values determined by elemental analysis.…”
Section: Catalyst Characterization the Actual Hpw/lzu1mentioning
confidence: 99%